Literation movement for leading schools: Best practice and leadership power - Zalik Nuryana; Agus Suroyo; Indah Nurcahyati; Farid Setiawan; Arif Rahman (International Journal of Evaluation and Research in Education (IJERE), 2020)
The school literacy movement is the first step of scientific development, aimed at enhancing science education. It has an important role in encouraging every citizen to have basic knowledge of the nature of science through active participation. This study aims to analyze the implementation of the School Literacy Movement program designated by the Ministry of Education and Culture due to the poor reading interest Indonesia students from several international surveys. The study was conducted at Al Mujahidin Muhammadiyah Middle School in Yogyakarta, using the qualitative method of data collection. The results show that the school literacy program is not only specific for reading and writing but for also other academics as activities such as numerals, science, digitalization, finance, culture, and citizenship. In conclusion, the implementation of a structured and systematic program positive impacts on the growth of literacy achievement for all school members from students, teachers, down to employees in Indonesia.